No Passport Required: Crossing Interdisciplinary Borders in an Australian Legal Clinic - Doris Bozin; Allison Ballard; Vicki de Prazer; Jenny Weekes (Laws, 2020)
How can disparate professions better collaborate in a legal clinic environment to improve the health and wellbeing, legal and social outcomes for patients/clients? In this paper, we explore how an intentional blurring of the boundaries between the health and legal professions in practice—between lawyers, general practitioners and psychologists, in particular—in the context of clinical legal education may result in better patient/client outcomes. We find that direct interdisciplinary professional referrals for patient/clients within a legal clinic environment can promote effective and timely therapeutic interventions for those with complex and interrelated legal and health problems. Drawing upon the literature around cross-disciplinary professional client referrals and two client case studies from a health–justice legal clinic environment in which doctors, psychologists and lawyers personally cross-refer patients with legal and health problems, we recommend some steps to break down the interdisciplinary borders so as to improve access to justice and health outcomes for vulnerable clients.